Work Incentives and Universal Credit Reform of the Benefit System in the United Kingdom - Pareliussen, Jon (OECD Publishing, 2013)
Under the Universal Credit reform, the main means-tested benefits except the Council Tax Benefit will be pooled into one single benefit with one single taper rate. The reform will give people better incentives to work, reduce complexity and contribute to reducing poverty. The reform could reduce the number of workless households by between 45 000 and 240 000 and increase labour supply by the equivalent of 15 000-85 000 full-time employees. Increased take-up and increased entitlements for low income families will further reduce poverty and increase equality. However, the cost of childcare remains high even after taking childcare benefits into account. Despite significant improvements, childcare expenses will continue to be a hurdle to progress in work for second earners and lone parents, even after the Universal Credit reform
Keywords: Social Issues/Migration/Health; Economics; United Kingdom